Coherence between Emotion and Facial Expression: Evidence from Laboratory Experiments. (January 2013) - Reisenzein, Rainer; Studtmann, Markus; Horstmann, Gernot
Evidence on the coherence between emotion and facial expression in adults from laboratory experiments is reviewed. High coherence has been found in several studies between amusement and smiling; low to moderate coherence between other positive emotions and smiling. The available evidence for surprise and disgust suggests that these emotions are accompanied by their "traditional" facial expressions, and even components of these expressions, only in a minority of cases. Evidence concerning sadness, anger, and fear is very limited. For sadness, one study suggests that high emotion–expression coherence may exist in specific situations, whereas for anger and fear, the evidence points to low coherence. Insufficient emotion intensity and inhibition of facial expressions seem unable to account for the observed dissociations between emotion and facial expression.